Cannabis use among a nationally representative cross-sectional sample of smokers and non-smokers in the Netherlands: results from the 2015 ITC Netherlands Gold Magic Survey. Issue 3 (3rd March 2019) - Fix, Brian Vincent; Smith, Danielle; O'Connor, Richard; Heckman, Bryan W; Willemsen, Marc C; Cummings, Michael; Fong, Geoffrey
Abstract : Objectives: Existing evidence shows that co-occurring use of tobacco and cannabis is widespread. Patterns of co-use of tobacco and cannabis may change as more jurisdictions legalise medicinal and/or recreational cannabis sales. This analysis examined predictors of current cannabis use and characterised methods of consumption among smokers and non-smokers in a context where cannabis use is legal. Setting: The 2015 International Tobacco Control Netherlands—Gold Magic Survey conducted between July and August 2015. Participants: Participants (n=1599; 1003 current smokers, 283 former smokers and 390 non-smokers) were asked to report their current (past 30-day) use of cigarettes and cannabis. Cigarette smokers reported whether they primarily used factory made of roll-your-own cigarettes. Those who reported any cannabis use in the last 30 days were asked about forms of cannabis used. X 2 and logistic regression analyses were used to assess relationships among combustible tobacco and cannabis use. Results: Past 30-day cannabis use was somewhat higher among current tobacco (or cigarette) smokers (n=57/987=5.8%) than among former or never smokers (n=10/288=3.5% and n=6/316=1.9%, respectively). Joints were the most commonly used form of cannabis use for both current cigarette smokers (96.9%) and non-smokers (76.5%). Among those who smoked cannabis joints, 95% current smokers and 67% of non-smokers reported that they 'always' roll cannabis with tobacco. Conclusions: In this Netherlands-based sample, most cannabis was reported to be consumed via smoking joints, most often mixed with tobacco. This behaviour may present unique health concerns for non-cigarette smoking cannabis users, since tobacco use could lead to nicotine dependence. Moreover, many non-cigarette smoking cannabis users appear to be misclassified as to their actual tobacco/nicotine exposure.